The effect of COVID-19 on the academic performance of Zayed University students in the United Arab Emirates - AlBlooshi, Sharifa; Smail, Linda; Albedwawi, Alyaa; Al Wahedi, Mariam; AlSafi, Maha (Frontiers in Psychology, 2023)
Purpose The outbreak of the coronavirus (COVID-19) pandemic led to significant changes across various sectors, including the field of education. In response to the pandemic, educational institutions worldwide, including Zayed University in the United Arab Emirates (UAE), transitioned to online learning. This study aimed to investigate the impact of COVID-19 on the academic performance of students in the UAE and their satisfaction with remote learning, while also examining gender differences in these variables. Methods This study used a quantitative research design in which a questionnaire was used to collect data. The study employed a snowball sampling method to recruit a total of 1,780 male and female students aged 18 and above from Zayed University in the UAE. The collected data were analyzed using appropriate statistical techniques. Results This study revealed that students at Zayed University maintained a good level of academic performance (M = 3.34, SD = 0.76) during the COVID-19 pandemic and were satisfied with online learning (M = 3.48, SD = 0.84) during the COVID-19 pandemic. A significant positive correlation was observed between students’ academic performance and their level of satisfaction with online teaching during the COVID-19 pandemic (p < 0.001). Furthermore, no significant differences were found between gender and both academic performance and level of satisfaction with online learning. Finally, we found that more males leaned toward online learning while more females leaned toward face-to-face learning. Conclusion This study contributes to understanding the impact of COVID-19 on students’ academic performance and satisfaction with remote learning in the UAE context. The findings highlight the significance of student satisfaction for successful online learning and emphasize the need for adequate resources and the maintenance of education quality.